Analysis of the Lost Circulation process for development of drilling operations in Al-Omar oil field – Syria - Farid, Tareq Ali (Journal of engineering sciences and information technology, 2023)
One of the major challenges confronting the oil and gas industries worldwide is lost circulation, which results in significant amounts of drilling non-productive time. Drilling fluid loss may result in additional drilling issues such as stuck pipe, borehole instability, or a potential well control event.Al-Omar field in Syria is one of the world's largest oil fields. When drilling through the Shiranish formation, wells in this field are highly susceptible to lost circulation problems. The lost circulation processes in Al-Omar Oil field are close to complete failure due to leakage. This issue is important in field development operations and is given great attention.If the process is carried out according to the correct course, there is expected to be a significant decrease in Non-Productive Time (NPT) resulting from the loss. On the other hand, this paper will consider the cost of remedy processes and the NPT relating to the remedy method used. The loss in the Shiranish layer comes from more than 700 oil wells drilled in Syria and is discovered using field sources and various engineering reports. Remedy processes were divided according to the field data into three losses: (1) partial loss, (2) severe losses, and (3) complete losses.In this paper, we use economic forecasts that are considered significant from an economic point of view when setting remedy processes. In addition, we employ the incoming probabilities method and remedy the costs of lost circulation in Al-Omar field in Syria. We perform hundreds of remedies on the three types of losses, calculate the Expected Monetary Value (EMVs) in all operations to reduce NPT and high costs, and choose the least costly method to process EMV that we can apply correctly and practically and is acceptable to remedy all types of losses. And if the losses continue after using the proposed solutions, we can suggest some changes in the design of the well to prevent losses.The methods used in dealing with the problem of lost circulation are some of the most significant challenges we face at Al-Omar oil field in Syria, and as a result, the data analysis process provides a clear path for the Syrian fields. It can also be used in other similar formations in the Middle East. It also applies to configurations with properties identical to Al-Omar oil field.
Keywords: Oil field drilling; Lost Circulation process; Al-Omar oil field; Syria